Metabolic and cardiovascular risk profiles and hepatitis C virus infection in rural Egypt. Issue 8 (6th September 2006) - Marzouk, D; Sass, J; Bakr, I; El Hosseiny, M; Abdel-Hamid, M; Rekacewicz, C; Chaturvedi, N; Mohamed, M K; Fontanet, A
Abstract : Background and aim: To investigate the relationship between lipid profiles and diabetes with past and chronic hepatitis C virus (HCV) infection among village residents of Egypt. Patients and methods: Fasting lipids and glucose profiles were compared among adults never infected with HCV (negative HCV antibodies), infected in the past (positive HCV antibodies and negative HCV RNA) and chronically infected (positive HCV antibodies and HCV RNA). Results: Of the 765 participants, 456 (59.6%) were female, and median age was 40 (range 25–88) years. Chronic HCV infection was present in 113 (14.8%) and past infection in 67 (8.8%). After adjustment for age and sex, participants with chronic HCV infection had lower plasma low density lipoproteins (LDL) cholesterol and triglyceride levels compared with those never infected (age and sex adjusted differences (95% CI) were −19.0 (−26.3 to −11.7) mg/dl and −26.2 (−39.0 to −13.3) mg/dl, respectively). In contrast, participants with cleared HCV infection had higher triglyceride levels compared with those never infected (age and sex adjusted difference (95% CI) was +16.0 (0.03 to 31.9) mg/dl). In multivariate analysis, participants with chronic HCV infection were more likely to have diabetes (OR 3.05, 95% CI 1.19 to 7.81) compared with those never infected, independent of LDL cholesterol levels. Conclusion: In conclusion, this community based study has shown that in a single population, chronic HCV infection is associated with glucose intolerance and, despite that, a favourable lipid pattern. An intriguing finding was the high triglyceride levels observed among participants with past infection, suggesting that elevated triglycerides at the time of acute infection may facilitate viral clearance.